Mr. Nick is a lunatic! - Gutman, Dan (Gutman, Dan. My weirdest school, 2016)
When the teachers of Ella Mentry School go on strike, A. J. and the gang meet a new principal who does not believe in rules and says that the students do not have to learn anything if they do not want to.